Pengaruh Intellectual Capital, Good Corporate Governance, Leverage dan Profitabilitas terhadap Nilai Perusahaan - Ika Laely Rahmawati; Sri Mulyani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the relationship between intellectual capital, good corporate governance, leverage, and profitability with company value. This study uses a quantitative method with secondary data collected from company financial reports available on the Indonesia Stock Exchange. The research sample consists of 71 non-cyclical sector companies. The analysis uses panel data processed with SPSS26. The results show that intellectual capital has no effect on company value, nor does good corporate governance have a significant effect on company value. Furthermore, leverage has a positive effect on company value, and profitability has a positive effect on company value. These findings emphasize the importance of optimizing leverage and profitability as key instruments for increasing company value. This also aims to evaluate good corporate governance policies in order to build market confidence without becoming a burden of administrative procedures. In addition, this study can be a reference for management to balance debt management and profit creation in order to maintain a positive market perception.